Maritime Heritage and Primary Education in Galicia (Spain) - Feijóo-Outumuro, Julia; Castro-Fernández, Belén (Clio. History and History Teaching, 2025)
This paper aims to demonstrate the social and educational relevance of maritime heritage as an element of social cohesion, symbolic recognition and cultural identity. The region of Galicia in north-west Spain is taken as a case study. This area is one of Europe’s most important fishing areas and has extensive maritime heritage. In order to contribute to the design of educational projects which foster links and emotional connections with the maritime environment, a mixed research method is employed to identify the degree to which maritime heritage is used in the education of Galician schoolchildren (aged 6-12). The results seem to confirm that, in spite of the importance of this type of heritage in Galicia, it is scarcely visible in the region’s schools, receiving very little attention in the curriculum. This could lead to indifference among citizens towards the sea as a heritage asset.